Expression of p16 and Ki67 in laryngeal squamous cell carcinoma and their clinical significance - Liu, Xue-Ying; Hanjing, Shangguan; Zhang, Bing-huang; Luo, Xian-Yang (Frontiers in Oncology, 2024)
ObjectiveThe objective of this study is to assess the prognostic value of Ki67 and p16 proteins in laryngeal cancer.Materials and methodsThis retrospective cohort analysis comprised 260 patients diagnosed with laryngeal cancer. Immunohistochemistry (IHC) was employed to assess the expression levels of p16 and Ki67, and their correlation with the survival time of laryngeal cancer patients was analyzed.ResultsThe Ki67 index level exhibited a significant association with the prognosis of laryngeal cancer. Patients with higher Ki67 index levels demonstrated shorter survival times, more severe pathological classification, and higher tumor stages (P < 0.05). Conversely, no significant differences in prognostic characteristics of laryngeal cancer were observed in the p16 (-/+) population (P > 0.05). The median survival times for patients with Ki67 index levels of 0-35%, 36-70%, and 70-100% were 3.54 years, 2.10 years, and 1.92 years, respectively. After adjusting for age, smoking, alcohol consumption, pathological classification, surgical intervention, recurrence, and metastasis, the risk of death for patients with Ki67 index levels of 70-100% was 2.0504 times higher than that of patients with Ki67 index levels of 0-35% (95% CI: 1.2997-3.2345, P = 0.0020).ConclusionThe Ki67 index level is strongly associated with survival time and the risk of death in laryngeal cancer, making it a valuable prognostic indicator. However, the prognostic value of p16 levels in laryngeal cancer is limited. These findings provide important insights for prognosis evaluation and treatment decision-making in patients with laryngeal cancer.